Assessment of physical fitness among people over 60 years of age - Ciesielski, Jakub; Perkowski, Radosław (Journal of Education, Health and Sport, 2024)
Introduction: An ageing of population is becoming more and more common. With age, the functionality and efficiency of the body decreases. As a result, the time spent by seniors on physical activity is shortened and physical fitness decreases. For this reason, the physical fitness of seniors should be regularly checked and they should be encouraged to take up physical activity. There are many proven and reliable tests used to assess physical fitness. Materials and methods: The study group consisted of 40 people (31 women and 9 men), aged 60-78 years. The tests used in following study were: the SPPB questionnaire, handgrip strength test, and arm and calf circumference measurements. An attempt was made to find sociodemographic factors that could influence the level of physical fitness. It was checked whether physical fitness and physical activity depend on age, gender and BMI. It was checked how much time older people spend on physical activity during the day and week. The study confirmed that physical fitness decreases with age. Results: Tests and interviews have shown that people who spend more than 60 minutes a day on physical activity achieve higher scores on the SPPB questionnaire. These results were applicable to both women and men. Studies in a larger and more diverse population would need to be repeated in order to further confirm these results and draw more conclusions.